Enforcement Of Laws Against Mining Resulting In Environmental Pollution Due To Mercury Liquids - Iksaldi Kadullah (Estudiante Law Journal, 2019)
Abstract: This study aims to find out law enforcement against mining resulting in environmental pollution due to mercury. This type of research is the dualism of normative-empirical legal research and this research uses an approach. Law Enforcement Against Mining Causes Environmental Pollution Due to Mercury Liquid that there are three first ways is preemtive law enforcement, namely by coaching on actors this aims to strive to prevent environmental damage by mercury liquids. Second is preventive efforts by the police and the government to countermeasures by making appeals against the dangers of mercury use for the environment. While the last is law enforcement action by repressive means by confiscating tools and materials owned by miners. Environmental pollution that occurs is the indecision of the local government to enforce the law against illegal mining that is already damaging the environment. For that, both local governments and village governments should provide education to the community, especially to miners not to do things that should cause environmental pollution, especially the use of mercury.